2021
DOI: 10.20914/2310-1202-2021-1-121-128
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of gluten-free flours in the production of functional products

Abstract: The scientific review article allows to evaluate the relevance of scientific research of gluten-free bakery and confectionery products produced on the basis of secondary types of flour and flour mixtures, modern sources of non-traditional types of fruit and berry raw materials, innovative technologies, functional ingredients, designed to maintain the health of the population suffering from gluten intolerance. Much attention is paid to the use of amaranth seed flour in bread production, which has a higher biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…One of the main goals of the food industry is the development of specialized bakery products for dietary and functional nutrition. The main types of flour used for the production of such bakery products are following types of flour: buckwheat, amaranth, rice, linen, maize, hemp, etc [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main goals of the food industry is the development of specialized bakery products for dietary and functional nutrition. The main types of flour used for the production of such bakery products are following types of flour: buckwheat, amaranth, rice, linen, maize, hemp, etc [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the studied indicators of leguminous crops revealed that legumes are characterized by a high content of protein, fat, and minerals [7][8][9]. These advantages of leguminous crops predetermine the prospects for the development and improvement of technology for processing legumes to create flour, and further use in the production of gluten-free confectionery.…”
Section: Introductionmentioning
confidence: 99%